The Slow Focus Mode in Plasma Focus for Fast Plasma Stream Nano-Materials Fabrication: Selection of Energy of Bombarding Particles by Pressure Control - Lee, S.; Saw, S. H. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
As a radiation source, the plasma focus (PF) operates in the time-matched regime (TMR). Maximum energy is pumped into the compression, resulting in large inductive voltages (Vmax), high temperatures, and copious multi-radiations. In this Fast Focus Mode (FFM), targets in front of the anode are subjected to strong bursts of fast ion beams (FIB), post-pinch fast plasma streams (FPS), followed by materials exploded off the anode by relativistic electron beams (REB). In INTI PF in hydrogen, as operational pressure (P) is increased beyond TMR, dynamics slow down, the minimum pinch radius ratio (kmin) increases, Vmax decreases, FIB reduces in energy per ion (U), in beam power (PFIB), and damage factor (DFIB), as operation moves from FFM into Slow Focus Mode (SFM). This pattern is the same for other gases, but for Ar, Kr, and Xe, radiative collapse becomes dominant, past the TMR. As P is increased further, there comes a point (slowest SFM or SSFM) where compression is so weak that the outgoing reflected shock barely reaches the incoming piston. At SSFM, kmin is maximum (typically > twice that at FFM), Vmax, PFIB, and DFIB are low, and we expect a significant reduction in anode boil-offs. However, FPS energy is near its highest. Operation near SSFM reduces FIB damage and anode sputters on-target, allowing the largest area of interaction, primarily with the FPS. The above is surmised from RADPF FIB code. Recent experiments in INTI PF confirm experimental observations (Rawat, private communication 2013) that such high-pressure operations produce a bigger area of more uniform interaction. This should improve the production of nano-materials, e.g., carbon nanotubes on graphite substrate. Operational pressure may be used to select FPS particle energy, enabling control of bombarding particle energy, in the range of tens to hundreds of eV, and thus contribute to making PF materials technology more of a science than the present state-of-the-art.